THE EFFECT OF ENTREPRENEURSHIP EDUCATION ON STUDENTS' SCOPE START-UP ACTIVITIES: The Effect of Entrepreneurship Education on Students’ Scope Start-up Activities - Chaabane, Dhekra; Boujelbene, Younes (APPS Publications, 2023)
The main aim of this article is to determine the effect of Entrepreneurial Education (EE) on students’ scope start-up activities (SSSA). The study sought also to examine the mediating role of three entrepreneurial characteristics as known subjective norm (SN), Entrepreneurial Attitude (EA), and Perceived Behavioral Control (PBC) between EE and SSSA. A total of 120 questionnaires were collected from students in three institutions of Sfax university. Relationships between the variables were evaluated using factor analysis, reliability, correlations, descriptive statistics, and regression. The findings show a positive and significant influence of entrepreneurship education on the three entrepreneurial characteristics (EA, SN, PBC) and consequently on the student-scope startup activities. Further implications and limitations are also discussed in this article. Keywords: entrepreneurship education; entrepreneurial attitude; subjective norms; Perceived Behavioral Control; students’ scope start-up activities (SSS).